Karakteristik penderita tuberkulosis paru relapse yang berobat di poli paru RSUP Sanglah Denpasar Bali periode Mei 2017 hingga September 2018 - Ni Nyoman Adi Widyastuti; I Made Bagiada; Putu Andrika (DiscoverSys Inc., 2019)
Introduction: Relapse pulmonary tuberculosis (TB) is a TB patient who has previously received TB treatment, and has been declared cured or complete treatment, was re-diagnosed with positive smear TB based on swab examination or culture. In Indonesia there are many cases of repeat treatment. 70% of them are relapse cases. So that research on the characteristics of pulmonary TB patients relapse is important.Â Method: This research is a cross sectional descriptive study where the source of the data comes from secondary data, namely medical records of patients with pulmonary TB patients relapse in pulmonary outpatient clinics at Sanglah General Hospital period May 2017 until September 2018.Result: The results of this study showed that there were 40 patients proven to have pulmonary TB relapse. Most of the patients have ages of 50 to 59 years (25.0%), male sex (55.0%), last education in high school (57.5%), as many as 27.5% of them work as entrepreneurs and 27.5% do not work , the range of BMI in relapse pulmonary TB patients is 13-31 kg / m2 to 28.04 kg / m2 with an average of 19.54 + 3.03 kg / m2, the most clinical complaints are cough (80%), the most common comorbidities are pneumonia (15%) and based on thorax X-ray results found that the most finding was a picture of pleural effusion (22.5%).Conclusion: Based on demographic characteristics, relapse pulmonary TB patients were dominated by age + 50 years with male sex, highschool education status, dominant in patients who did not work and had a low BMI. Based on clinical symptoms, coughing up phlegm, coughing up bleeding and chest tightness are common symptoms. Based on the accompanying comorbidities, pneumonia and heart failure that most often accompanying disease. The most common X-ray image found in relapse pulmonary TB patients is the presence of pleural effusion.